Investigation on interfacial properties and calculation models of bamboo scrimber-to-concrete bonding joint. (27th December 2021) - Liu, Wen; Liu, Chengyang; Liu, Mingxi; Xu, Feng; Li, Zhi
Highlights: Single-lap shear tests on bamboo scrimber-to-concrete bonding joints are carried out. Effective bond length exists for the bonding joints. The interfacial calculation models are constructed. Abstract: Bamboo scrimber is a biomass unidirectional fiber-reinforced composite material. This study takes single-lap shear (SLS) tests on bamboo scrimber-to-concrete bonding joints, in order to analyze the interfacial properties and construct the useful calculation models. The test results show that bamboo scrimber-to-concrete bonding specimens in this study all have peeling failure in concrete substrate, which initiates at the loaded end and develops towards to the free end; moreover, concrete strength, adhesive layer thickness, bamboo scrimber width and thickness all have clear effects on the interfacial behaviors; besides, there exists an effective bond length in the interfacial zone, which is very important to decide the interfacial properties. Then, according to the interfacial governing equations as well as with reference to the classical models of fiber reinforced polymers (FRP)-to-concrete bonding joints, the interfacial calculation models of bamboo scrimber-to-concrete bonding joints are constructed, which can be used to predict the maximum shear stress, fracture energy, effective bond length and finally debonding load. The research results are useful to design bamboo scrimber reinforced concrete structures.